DIPLOMASI KOMERSIAL INDONESIA TRADE PROMOTION CENTER (ITPC) DALAM MEMPROMOSIKAN KOPI KE AUSTRALIA PADA TAHUN 2023 - Syafa, Dara Nabila; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Coffee is one of the most potential natural resources in Indonesia. Coffee is present in the Australian market with many enthusiasts because of its diverse taste, Indonesia realizes national interests through trade promotion activities, market penetration, education that makes it easier for coffee exporters, and opens discussions on coffee trade opportunities in the Australian market. This study uses the concept of commercial diplomacy and the perspective of liberalism with a nation-state level of analysis. This concept will explain complex diplomatic and commercial relations, cooperation, and how to influence foreign economic policy. Commercial diplomacy is an activity carried out by representatives of countries with diplomatic status in order to promote business between the home country and the host country. The research method used is a qualitative method with data collection techniques obtained from literature studies. The results of this study indicate that the Indonesia Trade Promotion Center (ITPC) plays a very important role in promoting coffee to Australia in 2023 through various commercial diplomacy strategies according to Naray. Commercial diplomacy in the study applies several commercial diplomacy indicators that have been focused on by the author such as: Communication (Through Exhibitions), Referral (Through Business Meetings), Co-ordination (Through Coordination with Various Diplomatic Actors), Advocacy (Managing Exports by Following Australian Government Regulations). Keywords: Export, Coffee, Strategy, Promotion, Indonesia, Australia, Commercial Diplomacy